Evaluation of a High-Intensity Green Fluorescent Protein Fluorophage Method for Drug- Resistance Diagnosis in Tuberculosis for Isoniazid, Rifampin, and Streptomycin - Yu, Xia; Gu, Yunting; Jiang, Guanglu; Ma, Yifeng; Zhao, Liping; Sun, Zhaogang; Jain, Paras; O'Donnell, Max; Larsen, Michelle; Jacobs, William R.; Huang, Hairong (Frontiers in Microbiology, 2016)
A novel method for detecting drug resistance in Mycobacterium tuberculosis using mycobacteriophage ф2GFP10 was evaluated with clinical isolates. The phage facilitates microscopic fluorescence detection due to the high expression of green fluorescence protein which also simplifies the operative protocol as well. A total of 128 clinical isolates were tested by the phage assay for isoniazid (INH), rifampin (RIF), and streptomycin (STR) resistance while conventional drug susceptibility test, by MGIT960, was used as reference. The sensitivities of ф2GFP10 assay for INH, RIF and STR resistance detection were 100%, 98.2% and 89.3%, respectively while their specificities were 85.1%, 98.6 % and 95.8%, respectively. The agreement between phage and conventional assay for detecting INH, RIF and STR resistance was 92.2%, 98.4% and 93.0%, respectively. The ф2GFP 10-phage results could be available in 2 days for RIF and STR, while it takes 3 days for INH, with an estimated cost of less than $2 to test all the three antibiotics. The ф2GFP 10-phage method has the potential to be a valuable, rapid and economical screening method for detecting drug-resistant tuberculosis.